Acoustic conditions in open plan offices - Pilot test results - Witold Mikulski (Nofer Institute of Occupational Medicine, 2016)
Background: The main source of noise in open plan office are conversations. Office work standards in such premises are attained by applying specific acoustic adaptation. This article presents the results of pilot tests and acoustic evaluation of open space rooms. Material and Methods: Acoustic properties of 6 open plan office rooms were the subject of the tests. Evaluation parameters, measurement methods and criterial values were adopted according to the following standards: PN-EN ISO 3382- 3:2012, PN-EN ISO 3382-2:2010, PN-B-02151-4:2015-06 and PN-B-02151-3:2015-10. Results: The reverberation time was 0.33- 0.55 s (maximum permissible value in offices - 0.6 s; the criterion was met), sound absorption coefficient in relation to 1 m2 of the room's plan was 0.77-1.58 m2 (minimum permissible value - 1.1 m2; 2 out of 6 rooms met the criterion), distraction distance was 8.5-14 m (maximum permissible value - 5 m; none of the rooms met the criterion), A-weighted sound pressure level of speech at a distance of 4 m was 43.8-54.7 dB (maximum permissible value - 48 dB; 2 out of 6 rooms met the criterion), spatial decay rate of the speech was 1.8-6.3 dB (minimum permissible value - 7 dB; none of the rooms met the criterion). Conclusions: Standard acoustic treatment, containing sound absorbing suspended ceiling, sound absorbing materials on the walls, carpet flooring and sound absorbing workplace barriers, is not sufficient. These rooms require specific advanced acoustic solutions. Med Pr 2016;67(5):653-662